The structure of Ibìbìò determiner phrase (2022)
"The Determiner Phrase (DP) is a syntactic category headed by a determiner. Its internal structure has attracted scholarly attention across languages. Although, various aspects of Ìbìbìò grammar have been examined by scholarly works, the syntax of the Determiner Phrase has not been given much attention. This study, therefore, investigates the Determiner Phrase in Ìbìbìò with a view to examining its internal constituents and hierarchical structure. Primary data for the study were elicited through interviews with the aid of the Ibadan 400-word list and syntactic checklist while secondary data were collected from existing literature. Data were analysed qualitatively based on the DP hypothesis and Chomsky’s Minimalist Program. The study identified ten determiner elements in the language. They are numbers, particularisers, as well as cardinal and ordinal numerals. Some are marked for specificity or definiteness (e.g. étó ádò) while others are marked for indefiniteness (étó kèèd). The difference between the former and the latter is definiteness and indefiniteness triggered by the determiners kèèd ‘a’ and ádò ‘the’ respectively. Other determiners identified in the language are: articles, demonstratives, quantifiers, genitives, pronouns, and bare nouns. Based on the distribution of the internal constituents of the DP, the hierarchical structure of the Ìbìbìò Determiner phrase is- DP>PartP>NumP>PossP>Num’rP>DemP>NP. The study concludes that DPs take NP complements in Ìbìbìò.